(untitled) (Bangladesh Agronomy Journal, 2015)
An experiment was conducted at the Cotton Research Farm, Sreepur, Gazipur during 2009-10 growing season to maximize the benefit of cotton + mungbean intercropping system through appropriate planting arrangement of component crops in the system. Performance of eight different planting arrangements, such as 1, 2, 3 and 4 rows of mungbean in between single row of cotton and 4, 5, 6 and 7 rows of mungbean in between paired row cotton ware compared against their sole cropping. Intercropping and mungbean density reduced individual yield of cotton and mungbean compared to their sole cropping but increased equivalent yield of both cotton and mungbean. The highest seed cotton (2951 kg ha-1) and mungbean (3373 kg ha-1) equivalent yield was recorded from the paired row cotton +4-row mungbean. The land equivalent ratio of the same combination indicated 31% yield advantage over sole cropping. The same plating arrangement also recorded the highest gross return (Tk. 118039 ha-1), gross margin (Tk. 60220 ha-1) and BCR (2.04). Thus, the panting arrangement of paired row cotton and 4 rows of mungbean could be grown for higher productivity and economic return in the system. Bangladesh Agron. J. 2014, 17(1): 11-22